Simulation and analysis of innovative hand tool harvester - Razali, Mohd Hudzari; Salit, Mohd Sapuan; M. Abd Halim, Abdul Ssomad; Mohd Noor, Noordin Asimi; Muhammad, Hasbullah; Roslan, Syazili (Academic Journals, 2012)
There is a real need to develop a hand tool harvester since harvesting tubers of Dioscorea hispida (ubi gadong) is time tedious and consuming. The tubers were surrounded by roots, which were well gripped to the soil which made harvesting process difficult. Therefore, a new tool equipped with cutting device to cut the roots of D. hispida is required. The information from the experiments is used to model and simulate the tool in Computer Aided Design (CAD) environment. The solid modeling software solidworks was used for the design, modeling and simulation of the equipment and the finite element analysis to determine the stress, force and displacement were also conducted.